PENGARUH MOTIVASI BERPRESTASI DAN GAYA BELAJAR TERHADAPPRESTASI BELAJAR ASUHAN KEBIDANANIBU HAMIL PADAMAHASISWA KEBIDANANSTIKES BINA SEHAT PPNI MOJOKERTO - Ma’rifah, Asirotul (JURNAL KEPERAWATAN SEHAT, 2014)
Learning achievement is a measure of success in a learning process. Many factors affect a persons learning achievement. In this study only focused on achievement motivation factors and learning styles of students. Theoretically, learning achievements may be affected by the achievement motivation and learning style of the individual. Research Purposes: (1) Determine the effect of achievement motivation on learning achievement midwifery care of pregnant women (2) Determine the effect of differences in learning styles on learning achievement midwifery care of pregnant women (3) identifying interaction effect of achievement motivation and learning styles together on learning achievement midwifery care of pregnant women. Methods :The study design was a causal comparative research. Research target population is all students enrolled Midwifery third semester as a student active in the STIKes BinaSehatPPNI Mojokerto academic year 2013/2014, amounting to 171 people. Sample of 64 people selected by proportional cluster random sampling technique.Instrumen:There are two methods used to collect the data that is questionnaire and study documents such as documents the average value of the learning outcomes of midwifery care of pregnant women. Data were analyzed using two way ANOVA models Results: (1) There is a difference in learning achievement is very significant between students with high motivation with students who have low motivation with significance 0.002 < 0.05. ( 2 ) there is a difference of at least one of the differences of learning achievement pregnant women between students with a visual learning style , auditors and kinesthetic with significance 0.012 < 0.05 . (3) There is interaction between learning style and motivation to learn prestsai student with an F = 3.501 with a significance of 0.037 < 0.05. Conclusion: There is Determine the effect of achievement motivation and learning styles individually and jointly on learning achievement pregnant women in midwifery care midwifery students STIKes BinaSehat PPNI Mojokerto.Keyword: Achievement Motivation, Learning Styles, Learning Achievement Maternal Obstetric Care.